2013
DOI: 10.2174/1573401311309020004
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Restitution of Gut Barrier by Probiotics: Nutritional and Clinical Implications

Abstract: Probiotics are beneficial bacteria present in various dietary components and many of these colonize in the human and animal intestine. In the gut probiotics help the host by assisting in maintenance of normal mucosal homeostasis. Probiotics not only help maintain normal function of the gut mucosa, but also protect mucosa from injurious factors such as toxins, allergens and pathogens. The beneficial effect of probiotics is mediated by multiple mechanisms, including cytoprotection, cell proliferation, cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(70 citation statements)
references
References 120 publications
(122 reference statements)
1
58
0
1
Order By: Relevance
“…We have also tested the inhibition of BoNT/A binding using different commercial probiotic supplements, most showed inhibitory effects (data not shown). These results suggest that, consistent with other probiotic studies, the beneficial effects of probiotics are strain- and species-dependent [47,48]. The probiotic E. coli strain Nissle 1917 was however not available in the U.S. for use in comparison testing at the time of study.…”
Section: Discussionsupporting
confidence: 72%
“…We have also tested the inhibition of BoNT/A binding using different commercial probiotic supplements, most showed inhibitory effects (data not shown). These results suggest that, consistent with other probiotic studies, the beneficial effects of probiotics are strain- and species-dependent [47,48]. The probiotic E. coli strain Nissle 1917 was however not available in the U.S. for use in comparison testing at the time of study.…”
Section: Discussionsupporting
confidence: 72%
“…The mechanisms by which probiotics can influence the barrier function are also an area of interest, although many studies have shown that probiotics increase the barrier function by increasing mucus, antimicrobial peptides, and secretory IgA production, as well as increasing competitive adherence for pathogens, and the tight junctions (TJ) integrity of epithelial cells [55,56,57]. It is known that certain lactobacilli adhere to mucosal surfaces, inhibiting the attachment of pathogenic bacteria and enhancing the secretion of mucin.…”
Section: The Intestinal Microbiota Functionsmentioning
confidence: 99%
“…Firstly, certain probiotics can clearly exclude or inhibit pathogens, either through direct action or through influence on the commensal microbiota [2,4]. A second mechanism is the capacity of certain probiotic strains to enhance the epithelial barrier function by modulating signaling pathways, such as nuclear factor-κB (NF-kB), Akt and mitogen- activated protein kinase (MAPK)-dependent pathways, which lead to for example the induction of mucus [5], or increased tight junction functioning [6]. Thirdly, most probiotic strains can also modulate host immune responses, exerting strain-specific local and systemic effects [7].…”
Section: Introductionmentioning
confidence: 99%